Reconstruction of Holocene Paleoenvironment in Smeerenburgfjorden, northwest Svalbard based on benthic foraminifera and sedimentological investigations - Arnardóttir, Erna Ósk (UiT Norges arktiske universitet, 2015)
Two gravity cores JM06-024-GC3 and JM07-049-GC1 from Smeerenburgfjorden at the northwestern corner of Svalbard have been investigated for the distribution pattern of the benthic foraminiferal faunas. The oxygen and carbon isotope values in benthic foraminifera were analysed and together with other proxy data such as ice rafted debris (IRD), were used in order to reconstruct the paleoceanography and the paleoenvironment. The data are compared to several other records from the western and northern Svalbard margin. The results indicate high degree of variability between inflow of the warmer and saline Atlantic Water to the cold and fresh Arctic and the Polar Water in the area during the Holocene. The distribution patterns of the stable isotopies, the IRD and the benthic foraminifera indicate a concomitant temperature change around 5000 cal yr. BP. This temperature change is a result of a general cooling of the bottom water during the early Holocene. Conditions during the last 2000 years have been unstable, indicating an episodic inflow of Atlantic Water. The concentrations of calcareous and agglutinated benthic foraminifera vary in the late early Holocene, indicating bottom water oscillations between warmer and colder water masses. These oscillations indicate the repeated intrusion of the warmer Atlantic Water to the cold Arctic Water during the last 2000 years BP. The data indicates an interaction between the flow of the Atlantic Water and the amount of polar melt water and sea-ice.